TRANSFORMASI FILOSOFI NITENI, NIROKKE, NAMBAHI DALAM MENDESAIN INOVASI PEMBELAJARAN INTERAKTIF GENERASI ALFA - Charissa Muthia Wibowo; Jesy Marwana; Ignatius Ario Sumbogo; Aulia Sandra Maudina; Naysila Eka Julianti; Dara Salsabila Rianti (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
The development of the digital era in the world of education demands a learning ecosystem that is not only interactive and cutting-edge, but also remains rooted in local wisdom. The main problem in this research is the challenge of 21st-century education where digital technology penetration often does not correlate with the depth of cognitive processes and local values, necessitating a strong methodological framework to bridge technological sophistication with learning effectiveness. This research aims to design interactive learning innovations for Alpha Generation, who are known to be active and tech-savvy, by transforming Javanese philosophy from Ki Hadjar Dewantara's thoughts, namely Niteni, Nirokke, and Nambahi, into modern learning that aligns with the current